Crise do cuidado no Brasil?: uma análise da organização dos trabalhos de cuidados no âmbito jurídico brasileiro - Gabriela Dantas Rubal (2024)
This research examines the presence of the care crisis in Brazil and its nexus with Labor Law, through an analysis of the organization of care labor in the country considering sociodemographic trends and global phenomena. Unlike nations in the global North, Brazil has not encountered a deficit in care; conversely, it stands as one of the sectors with the highest rates of employability in the sector. However, the observed trend is the gradual increase in demand for care, accompanied by the process of commodification and professionalization of these practices. The historical and socioeconomic particularities of Brazil place the country in a controversial position in this debate. It can be said that the care crisis in the country behaves differently from other countries in the global North and is structured through its unique markers. mark the professions that are part of the care halo, characterized by informality, low wages, limited social safeguards, weak legal statuses, and insecurity. Within this framework, the legal treatment accorded to care labor in Brazil is intricate and insufficient for the workers’ needs. This has been an area systematically excluded from regulations or, when included, legitimized in a way that maintains precarious or less beneficial working conditions for laborers. Using the concept of care halos, five professions were analyzed, situated within each of the five circles constituting the organization of care as labor in Brazil: personal caregivers, domestic cleaners, nursing staff, beauty practitioners, and outsourced cleaning aides. Although governed by different regulations, all these occupations have in common the precariousness of their work justified by a legal discourse that validates social regression and the violation of labor rights. Thus, labor law has been used as a tool within the context of the Brazilian care crisis to ensure that the demand for care is met at the lowest conceivable cost. This situation of intense labor unprotectedness, coupled with a neoliberal political agenda, can be understood as a legal strategy adopted to maintain the conditions of the Brazilian care market and deny labor rights. Despite its deficiencies, Labor Law plays labor law plays an important and historical role in safeguarding fundamental social rights. Advocating for it constitutes part of a process of reclaiming and reviewing what can be altered from a feminist and critical labor epistemology what can be changed from a feminist and critical labor epistemology that places care at the center of discussions.